Stress assisted corrosion in a crude oil production tube made from L80 steel. (April 2017) - Ravindranath, K.; Al-Wakaa, B.; Tanoli, N.
Abstract: Failure investigation was carried out on a crude oil production tube made of L80 steel. The failure appeared like a long crack, but on closer examination, it was found to have formed by localized thinning along the longitudinal axis of the tube. Remaining areas of the tube was unaffected and without any appreciable corrosion. Deep depressions and crack-like features were observed in the cross section of the sample near the location of thinning. Analysis of the corrosion products taken from an affected location revealed that the corrosion products were comprised of sulphides of iron. Microhardness measurements made on the tube indicated relatively higher hardness at the affected locations. The results of electrochemical corrosion tests conducted in 0.2 M sodium chloride and 0.2 M sodium chloride + 0.01 M sodium thiosulphate solutions showed a higher corrosion rate for the sample at the affected location. The investigation concluded that the failure of the tubing was due to stress assisted corrosion (SAC). The tube at the failed location was at an elevated stress due to leaning or resting of the pump rod, which resulted in the accelerated corrosion. Highlights: Failure investigation was conducted to identify root cause of failure of a crude oil production tube. Failure due to localized thinning Increased hardness near the location of failure Failure of the tube was due to stress assisted corrosion.